2013
DOI: 10.1021/ja407508v
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Silicon Nanoparticles with Ultrabright Photoluminescence and Single-Exponential Decay for Nanoscale Fluorescence Lifetime Imaging of Temperature

Abstract: In this Communication, we report fabrication of ultrabright water-dispersible silicon nanoparticles (SiNPs) with quantum yields (QYs) up to 75% through a novelly designed chemical surface modification. A simple one-pot surface modification was developed that improves the photoluminescent QYs of SiNPs from 8% to 75% and meanwhile makes SiNPs water-dispersible. Time-correlated single photon counting and femtosecond time-resolved photoluminescence techniques demonstrate the emergence of a single and uncommonly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
152
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(158 citation statements)
references
References 30 publications
5
152
0
1
Order By: Relevance
“…44249 In our previous work, we produced novel Si NCs with unprecedented ultrabright fluorescence and single-exponential decay. 23 According to the time-resolved PL dynamics, we demonstrated that no fast PL decay component was present in the range of *These authors contributed equally to this work sub-picosecond to hundreds of nanoseconds in these ultrabright Si NCs. In addition, their steady-state optical properties, i.e., PL quantum yield (QY), excitation-and temperature-dependent PL behaviors, are closely related to the surface organic agents.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…44249 In our previous work, we produced novel Si NCs with unprecedented ultrabright fluorescence and single-exponential decay. 23 According to the time-resolved PL dynamics, we demonstrated that no fast PL decay component was present in the range of *These authors contributed equally to this work sub-picosecond to hundreds of nanoseconds in these ultrabright Si NCs. In addition, their steady-state optical properties, i.e., PL quantum yield (QY), excitation-and temperature-dependent PL behaviors, are closely related to the surface organic agents.…”
Section: Introductionmentioning
confidence: 87%
“…In a typical synthesis of unmodified Si NCs with surface Si-Cl bands (Cl-Si NCs), 23 0.17 g of sodium and 0.75 g of naphthalene were stirred in 20 mL of glyme for approximately 3 h to produce sodium-naphthalide. Then, 0.20 mL of SiCl 4 was added dropwise.…”
Section: Preparation Of Si Ncsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, recent observations suggest that certain electron donating, nitrogen containing species can drastically improve the blue emitting quantum yield of silicon quantum dots significantly. i.e., Li et al showed that performing only surface modification with electron donors containing nitrogen drastically improves the emission quantum yield of SiQDs to 50-75% [122]. (Figure 8) This surprising finding was proven by the Sun group [123], where ultrafast microscopy was used to indicate that this high quantum yield emission is indeed related to the surface trap states.…”
Section: Preparation and The Impacts Of Surface Chemistrymentioning
confidence: 95%